An Explanation Based on Energy-Related Changes for Blue Mussel Mytilus edulis Coping With Seawater Acidification - Guo, Ying; Zhou, Bin; Sun, Tianli; Zhang, Yaya; Jiang, Yongshun; Wang, You (Frontiers in Physiology, 2021)
As ocean acidification (OA) is gradually increasing, concerns regarding its ecological impacts on marine organisms are growing. Our previous studies have shown that seawater acidification exerted adverse effects on physiological processes of the blue mussel Mytilus edulis and the aim of the present study was to obtain energy-related evidences to verify and explain our previous findings. Thus, the same acidification system (pH: 7.7 or 7.1; acidification method: HCl addition or CO2 enrichment; experimental period: 21 d) was set up, and the energy-related changes were assessed. The results showed that the energy charge (EC) and the gene expressions of cytochrome C oxidase (COX) reflecting the ATP synthesis rate increased significantly after acidification treatments. What’s more, the mussels exposed to acidification allocated more energy to gills and hemocytes. However, the total adenylate pool (TAP) and the final adenosine triphosphate (ATP) in M. edulis decreased significantly, especially in CO2 treatment group at pH 7.1. It was interesting to note that, TAP, ATP and COXs gene expressions in CO2 treatment groups were all significantly lower than that in HCl treatment groups at the same pH, verifying that CO2-induced acidification exhibited more deleterious impacts on M. edulis and ions besides H+ produced by CO2 dissolution were possible causes. In conclusion, energy-related changes in M. edulis responded actively to seawater acidification and varied with different acidification conditions, while the constraints they had at higher acidification levels suggest that M. edulis will have a limited tolerance to increasing OA in the future.